Precision medicine: The use of tailored therapy in primary immunodeficiencies - Pinto, Marta Valente; Neves, João Farela (Frontiers in Immunology, 2022)
Primary immunodeficiencies (PID) are rare, complex diseases that can be characterised by a spectrum of phenotypes, from increased susceptibility to infections to autoimmunity, allergy, auto-inflammatory diseases and predisposition to malignancy. With the introduction of genetic testing in these patients and wider use of next-Generation sequencing techniques, a higher number of pathogenic genetic variants and conditions have been identified, allowing the development of new, targeted treatments in PID. The concept of precision medicine, that aims to tailor the medical interventions to each patient, allows to perform more precise diagnosis and more importantly the use of treatments directed to a specific defect, with the objective to cure or achieve long-term remission, minimising the number and type of side effects. This approach takes particular importance in PID, considering the nature of causative defects, disease severity, short- and long-term complications of disease and but also of the available treatments, with impact in life-expectancy and quality of life. In this review we revisit how this approach can or is already being implemented in PID and provide a summary of the most relevant treatments applied to specific diseases.